Les aspects économiques de la protection de la société - Sullivan, Richard (L'Actualité économique)

(untitled) (HEC Montréal, 1974)
AbstractIn this paper, the author describes some views that economists have of the problems of criminology together with the means accessible to them by which they attempt to answer certain interesting questions. Sketches of the economic arguments which are challenging a dominant view of the theory of criminal law and challenging as well the concept of "rehabilitation" are presented. The author proposes to review, briefly, the arguments for a systems approach and to outline new "industry" approaches to criminology problems. Finally, he tries to demonstrate why many traditional criminology studies are obsolete and he indicates in passing, the reason why the displacing of crime in time is a social benefit.